2008
DOI: 10.1074/mcp.m700258-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 2,3,7,8-Tetrachlorodibenzo-p-dioxin-induced Proteome Changes in 5L Rat Hepatoma Cells Reveals Novel Targets of Dioxin Action Including the Mitochondrial Apoptosis Regulator VDAC2

Abstract: As part of a comprehensive survey of the impact of the environmental pollutant and hepatocarcinogen 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) on the proteome of hepatic cells, we have performed a high resolution twodimensional gel electrophoresis study on the rat hepatoma cell line 5L. 78 protein species corresponding to 73 different proteins were identified as up-or down-regulated following exposure of the cells to 1 nM TCDD for 8 h. There was an overlap of only nine proteins with those detected as altered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 98 publications
(89 reference statements)
4
24
0
1
Order By: Relevance
“…However, Aroclor 1254 significantly induced the expression of the glutathione S-transferase Mu1 (GSTM1) gene, which is regulated through the ARE/EpRE (49), in the gills and digestive tract of the abalone Haliotis discus (50). Moreover some studies on rat hepatoma cells have reported that TCDD, whose chemical structure is similar to co-planar PCBs, induced the expression of different proteins in an ARE-dependent manner (51,52). Thus, the up-regulation of antioxidant enzymes such as Prx I with AREcontaining gene promoters is compatible with the hypothesis that PCBs could induce oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, Aroclor 1254 significantly induced the expression of the glutathione S-transferase Mu1 (GSTM1) gene, which is regulated through the ARE/EpRE (49), in the gills and digestive tract of the abalone Haliotis discus (50). Moreover some studies on rat hepatoma cells have reported that TCDD, whose chemical structure is similar to co-planar PCBs, induced the expression of different proteins in an ARE-dependent manner (51,52). Thus, the up-regulation of antioxidant enzymes such as Prx I with AREcontaining gene promoters is compatible with the hypothesis that PCBs could induce oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The isoform truncated Bet v 1.0101 did increase in expression upon ripening of the pollen, however this minor truncated Bet v 1.0101 isoform represented <5% of total Bet v 1 isoforms. The identity of the spots was confirmed with LC-MS after tryptic digest (Sarioglu et al, 2008), and if possible, by comparison with recombinant proteins. Also, our antibodies did not recognize the hypoallergenic isoform Bet v 1.0401 (Bet v 1 d), similar to a pool of human serum (data not shown) and as reported by others (Friedl-Hajek et al, 1999;Erler et al, 2011).…”
Section: The Role Of Bet V 1 Isoformsmentioning
confidence: 99%
“…Spots were quantified using Proteomweaver software (Definiens, Munich, Germany) and expressed as relative % of the sum of all intensities. Punched spots were identified by tryptic digestion and analysis by mass spectrometry as described by Sarioglu et al (2008).…”
Section: Bet V 1-isoform Analysismentioning
confidence: 99%
“…Some investigators, using two-dimensional gel electrophoresis to determine placental proteins, showed that rat placentas exposed to TCDD were in a hypoxic state at the end of pregnancy (Ishimura et al, 2002). Analysis of the changes in the rat hepatoma cell proteome indicated a mechanism by which TCDD may affect cellular homeostasis and survival (Sarioglu et al, 2008).…”
Section: 378-tetrachlorodibenzo-p-dioxin (Tcdd) Is a Ubiquitouslymentioning
confidence: 99%